نماذج التأخير والضياع الماركوفية في شبكات البيانات - جركس تاج الدين; معترماوي عدنان; ناصر غسان (Latakia University Journal -Engineering Sciences Series, 2019)
تستخدم نظرية الترتيل بشكل واسع لتحليل شبكات اتصالات البيانات المؤلفة من عقد تبديلية مرتبطة فيما بينها بواسطة وصلات النقل ويتم تحليل شبكات البيانات بفصلها إلى نظم جزئية وتحليل كل نظام جزئي بشكل منفرد باستخدام أحد نماذج الترتيل المعروفة. يقدم هذا البحث دليلاً عملياً لتحليل التأخير والضياع وفق منهجية جديدة ومتكاملة لشرح وعرض وتحليل أسس نظرية الترتيل ونماذج الترتيل الماركوفية في شبكات البيانات. يقوم البحث بدراسة وتحليل ومقارنة نماذج الترتيل الماركوفية الأساسية مع التركيز على التأخير والضياع كمقياسين هامين من مقاييس جودة الخدمة والأداء في شبكات البيانات. يوضح البحث كيفية استخدام سلاسل ماركوف لاستنتاج الحالة المستقرة لنماذج الترتيل الماركوفية الأساسية واستنتاج الصيغ الرياضية لمقاييس الأداء المختلفة لهذه النماذج. كما يتضمن البحث استنتاجات وتوصيات مناسبة تساعد في تطوير وإنشاء نماذج أخرى بوجود فرضيات معينة. The Queuing Theory is widely used for the analysis of data communication networks consisted of switched nodes. The analysis of data networks is based on method of decomposition where the total network is broken up into subsystem and the subsystems are analyzed individually by using one of the well known queuing models. This paper provides a practical guide to analysis the delay and loss according to a new integrated method to explain, show, and analyze the queuing theory basics and Markovian queuing models in the data networks. The paper investigates, analyzes, and compares the basic Markovian queuing models, and also focuses on analyzing the delay and loss as two important measures of the quality of service and performance in the data networks. The paper has conclusions and recommendations which help in the development and establishment other queuing models with specific assumptions.